Band Alignment in As‐Transferred and Annealed Graphene/MoS2 Heterostructures. Issue 2 (10th September 2019) - Romanov, Roman I.; Slavich, Aleksandr S.; Kozodaev, Maxim G.; Myakota, Denis I.; Lebedinskii, Yuri Y.; Novikov, Sergey M.; Markeev, Andrey M.
Abstract : The band alignment in the graphene/MoS2 van der Waals heterostructures (vdWHs) is investigated by Raman spectroscopy and X‐ray photoelectron spectroscopy (XPS) to understand the transfer‐ and annealing‐induced change of electronic properties. Raman spectroscopy indicates that partial electron redistribution between the MoS2 and graphene layers occurs when brought into contact, resulting in a hole concentration decrease in graphene from 1 × 10 13 to 7 × 10 12 cm −2 . The additional thermal annealing at 400 °C further decreases the hole concentration down to 3 × 10 12 cm −2 and leads to a MoS2 valence band offset increase by 0.2 eV. The annealing procedure also results in a visible decrease in adsorbed carbon‐ and oxygen‐containing contaminants, and this decrease is clearly detected by XPS. Thus, the combination of Raman spectroscopy and XPS provides a powerful diagnostic tool for the electronic properties at each stage of vdWHs preparation, allowing the attainment of 2D vdWHs with the desired properties. Abstract : Herein, the influence of the transfer procedure and post‐transfer annealing on the electronic properties of the graphene/MoS2 van der Waals heterostructures (vdWH) is shown. The electron redistribution between MoS2 and graphene layers, as well as a decrease in adsorbed contaminants, occurs during the annealing procedure. The combination of Raman spectroscopy and X‐ray photoelectron spectroscopy is a powerful diagnostic tool during heterostructure preparation.